2017
DOI: 10.1371/journal.pone.0187009
|View full text |Cite
|
Sign up to set email alerts
|

The Inventory of Depressive Symptomatology Self Report (IDS-SR): Psychometric properties of the Indonesian version

Abstract: BackgroundDepression screening and examination in Indonesia are highly challenging due to the disproportionately low number of mental health professionals in comparison to the Indonesian population. Self-report questionnaires on depression are cost-effective and time-efficient. The current study investigates the psychometric properties of the Indonesian Inventory of Depressive Symptomatology Self Report (IDS-SR).MethodsThe participants were 904 Indonesians (aged 16–61; 50.2% female), recruited via an online su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“… a Reliability of the Indonesian version of the IDS-SR from the original paper ( Arjadi et al, 2017 ). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a Reliability of the Indonesian version of the IDS-SR from the original paper ( Arjadi et al, 2017 ). …”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the Inventory of Depressive Symptomatology Self Report (IDS-SR) was used as a valid and reliable tool to measure depression level ( Rush et al, 1996 ; Rush et al, 1986 ) as a specific illness characteristic in this study. In the current study, we used the Indonesian version of the IDS-SR ( Arjadi et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome was the self-reported level of depressive symptoms 10 weeks after baseline, as measured by the PHQ-9, which consists of nine items with scores ranging from 0 to 27. 6 Secondary outcomes were PHQ-9 scores at 3 months and 6 months; remission of a depressive episode based on the SCID-5 at 10 weeks; 19 and depressive symptoms measured by the Indonesian version of the Inventory of Depressive Symptomatology Self Report, 20 fear and avoidance level as measured by the Fear Questionnaire, 21 perceived social support as measured by the Multidimensional Scale of Perceived Social Support, 22 and quality of life as measured by the brief version of the WHO Quality of Life 23 at 10 weeks, 3 months, and 6 months. A detailed description of the assessments is available in the trial protocol; 6 mediation analyses of potential mechanisms will be reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaires for assessing PGD, PTSD and PTG were translated from English into Bahasa Indonesia with a forward translation by a bilingual public health medical doctor and a backward translation by another independent bilingual public health medical doctor. The translation of the depression questionnaire (QIDS) was derived from a previous study conducted in Jakarta (Arjadi, Nauta, Utoyo, & Bockting, 2017). After this, the translated questionnaires underwent a critical review process focusing on the comprehensibility, relevance and cultural appropriateness consisting of a consultation with CL and two focus groups including the research assistants, public health staff, AP and MD (one before the administering of the pilot interviews and one after the pilot of 20 administered interviews and three more in-depth interviews).…”
Section: Methodsmentioning
confidence: 99%
“…The Quick Inventory of Depressive Symptomatology (QIDS-SR) is a 16-item questionnaire available in a self-rating format (Rush et al, 2003). This questionnaire includes a subset of questions of the Indonesian Inventory of Depressive Symptomatology Self Report (IDS-SR) which is known to have good validity and reliability in a sample of Javanese participants (Arjadi, Nauta, Utoyo, & Bockting, 2017). The items are scored in a 4-point Likert scale.…”
Section: Traumatic Grief Inventory Self-report (Tgi-sr) the Traumatic Griefmentioning
confidence: 99%